2017
DOI: 10.4300/jgme-d-16-00417.1
|View full text |Cite
|
Sign up to set email alerts
|

Transgender-Related Education in Plastic Surgery and Urology Residency Programs

Abstract: Background With increasing public awareness of and greater coverage for gender-confirming surgery by insurers, more transgender patients are likely to seek surgical transition. The degree to which plastic surgery and urology trainees are prepared to treat transgender patients is unknown.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
56
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
6
2
1

Relationship

3
6

Authors

Journals

citations
Cited by 83 publications
(57 citation statements)
references
References 12 publications
1
56
0
Order By: Relevance
“…In a study of undergraduate medical education in the USA and Canada in 2009-2010, only 30.3% of the 150 medical schools surveyed reported teaching about gender transitioning [77]. Gaps in residency programs in the USA have been described for Emergency Medicine [78], Urology [79] and Plastic surgery [80]. A survey of 15 Australian and New Zealand medical schools found that teaching about gender and gender identity is varied across schools, with seven respondents (47%) unsure about what is taught [81].…”
Section: What Are the Gaps In Curricula?mentioning
confidence: 99%
“…In a study of undergraduate medical education in the USA and Canada in 2009-2010, only 30.3% of the 150 medical schools surveyed reported teaching about gender transitioning [77]. Gaps in residency programs in the USA have been described for Emergency Medicine [78], Urology [79] and Plastic surgery [80]. A survey of 15 Australian and New Zealand medical schools found that teaching about gender and gender identity is varied across schools, with seven respondents (47%) unsure about what is taught [81].…”
Section: What Are the Gaps In Curricula?mentioning
confidence: 99%
“…In a survey of emergency medicine residency program directors, Moll et al 20 found that most programs did not contain lesbian, gay, bisexual, and transgender (LGBT)-specific curricular content. Related studies looking at undergraduate medical training, 21 various residency programs, [22][23][24][25] and public health schools 8 describe similar results. Lack of healthcare provider education is an identified barrier to accessing equitable healthcare for members of the SGM communities, 11,[26][27][28][29] highlighting the need for more research and formalized inclusion within medical training.…”
Section: Résumémentioning
confidence: 72%
“…Few studies have assessed the presence of SGM education within medical and healthcare provider curricula, so no validated surveys are available. 8,9,[20][21][22][23][24][25] Components of the literature, specifically an article by Burns et al, 38 aided the design and creation of a 32-item questionnaire (eAppendix, available as Electronic Supplementary Material), composed of both open and closed questions. Using an iterative process, a total of 12 individuals consisting of healthcare providers and SGM-identified people from within our local network of colleagues, researchers, and community members provided feedback to develop and refine the survey instrument.…”
Section: Instrument Developmentmentioning
confidence: 99%
“…Education on the care of sexual and gender minority patients has been found to be lacking not only in medical education and medical residency programs, but in predoctoral dental education. [17][18][19][20][21][22][23][24][25][26][27][28][29][30][31][32] For this reason, many providers may be uncomfortable with the delivery of care to transgender people.…”
mentioning
confidence: 99%